2011
DOI: 10.1016/j.ijdevneu.2011.05.010
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of the SNAT2 amino acid transporter during the development of rat cerebral cortex

Abstract: The sodium-coupled neutral amino acid transporter 2 (SNAT2) is a protein that is expressed ubiquitously in mammalian tissues and that displays Na(+), voltage and pH dependent activity. This transporter mediates the passage of small zwitterionic amino acids across the cell membrane and regulates the cell homeostasis and its volume. We have examined the expression of SNAT2 mRNA and protein during the development of the rat cerebral cortex, from gestation through the postnatal stages to adulthood. Our data reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…SNAT2 is expressed ubiquitously in mammalian tissues and displays Na + -, voltage- and pH-dependent activity [ 35 ]. SNAT2 mRNA can be detected in the duodenum, jejunum and ileum of piglets by real-time quantitative PCR, which most likely reflects the reported system A activity [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNAT2 is expressed ubiquitously in mammalian tissues and displays Na + -, voltage- and pH-dependent activity [ 35 ]. SNAT2 mRNA can be detected in the duodenum, jejunum and ileum of piglets by real-time quantitative PCR, which most likely reflects the reported system A activity [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the adaptive regulation of SNAT2 is not limited to the effects of system A substrates. Phenylalanine, tyrosine, and tryptophan also suppress system A [ 35 ], while glutamate, arginine and leucine enhance SNAT2 mRNA expression ( Fig 7 ), which may be due to the function of SNAT2 as a nutrient receptor [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both SNAT2 and SLC22A7 are transmembrane carriers. SNAT2 is dependent on the extracellular sodium ion concentration, and its best transport substrate is alanine, the most widely distributed transport protein in the family; SLC22A7 is a known cotransporter of sodium and phosphate, and can transport organic anions [ 66 , 67 , 68 ]. Moreover, KIF3B is a class of protein macromolecules with cellular motor function and involved in power supply (energy generated by ATP hydrolysis) for intracellular material transport, replication of DNA genetic material, transcription and translation of genetic material, and cell division [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is interesting to note that four of this group (PCDG4, SC6A6, S38A4, and S38A2; Table 1 ; Supplementary Table S10 ) are involved in neurotransmission activities and had their abundances reduced by LG. S38A2 and S38A4 are two sodium-coupled neutral amino acid transporters and S38A2 regulates the amino acid pool as well as the recycling of the neurotransmitter (Hatanaka et al, 2000 , 2001 ; Angelina et al, 2011 ) while SC6A6 is sodium-dependent taurine and beta-alanine transporter as well as a neurotransmitter transporter (Tomi et al, 2008 ). It has been demonstrated that hypoxia diminishes the expression and function of system A (alanine-preferring) amino acid transporters (Nelson et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%